Financialization and Level of Happiness in the Context of Sustainable Development. The Case of Central and Eastern European Countries - Aleksandra Ostrowska; Bogdan Włodarczyk (Finanse i Prawo Finansowe)
The purpose of the article. The article aims to identify and assess the impact of the financialization process on the level of happiness as an effect of sustainable development in selected Central and Eastern European countries in 2012–2022.